Recent technologies for cashew production towards zero hunger - Nayak, M. G.; Muralidhara, B.; Preethi, P. (Indian Farming, 2018)
Cashew has concurred the highest status in global market because of its countable nutritive status. Low productivity reflected with high cost makes cashew nuts not available for middle and lower class of people. The improved productivity will increase the per caput consumption and best solution to overcome malnutrition. The above techniques are found suitable to increase cashew productivity two-to three-fold and considered as superlative solution for food security.